Proceedings of 2019 international conference on optoelectronics and measurement conference proceedings - Peng, Yingquan; Dong, Xinyong (Springer, 2021)
This book presents high-quality papers from the 2019 International Conference on Optoelectronics and Measurement (ICOM2019) which was held on November 28–30, 2019, in Hangzhou, China. It focuses on the latest developments in the fields of optics, photonics, optoelectronics, sensors, and related measurement technology. Being closely related to either the key device technology or the important commercial applications, topics of fiber optics, photodetectors, sensors, and measurement technology are of particular interest for the readers. The book contains the illustrations of advanced device technologies, measurement principles, as well as scientific and technological conclusions of the great reference value. The readers will gain deep insight into the latest development in the related fields, obtain important technical data and scientific conclusions, and inspire new ideas for their research.